DINAMIKA PERKEMBANGAN ILMU DALAM ISLAM SERTA STATUSNYA DALAM PERKEMBANGAN PERADABAN MODERN - Muhammad Zainal Abidin (Fakultas Ushuluddin dan Humaniora UIN Antasari Banjarmasin, 2012)
This paper studies about the history and the dynamic of knowledge developing in Islam.The glorious of Islamic civilization which were signed by the advance of knowledgedeveloping around 7th to 13th centuries was not something hapened by an accident,but through long process and it was related with the prestige of muslims in field ofknowledge. In the centuries that called as the golden age of Islam, muslim civilizationbecome the central of world civilization and give the high contribution in emerging themodern western civilization. While, in next phase when muslim become underdevelopingcountries it was also related with the status on knowledge that marginalized and stagnantedin inmuslim world. There were many theories and argumentations from many expertsthat stated about the factors caused the falling of muslim. The falling of muslim peoplein same time is also the problem of mainkind together, because the western moderncivilization was ambigious in understanding the concept of knowledge.